Postarrest Steroid Use May Improve Outcomes of Cardiac Arrest Survivors. Issue 2 (February 2019) - Tsai, Min-Shan; Chuang, Po-Ya; Huang, Chien-Hua; Tang, Chao-Hsiun; Yu, Ping-Hsun; Chang, Wei-Tien; Chen, Wen-Jone
Abstract : Objectives: To evaluate the ramifications of steroid use during postarrest care. Design: Retrospective observational population-based study enrolled patients during years 2004–2011 with 1-year follow-up. Setting: Taiwan National Health Insurance Research Database. Patients: Adult nontraumatic cardiac arrest patients in the emergency department, who survived to admission. Interventions: These patients were classified into the steroid and nonsteroid groups based on whether steroid was used or not during hospitalization. A propensity score was used to match patient underlying characteristics, steroid use prior to cardiac arrest, the vasopressors, and shockable rhythm during cardiopulmonary resuscitation, hospital level, and socioeconomic status. Measurements and Main Results: There were 5, 445 patients in each group after propensity score matching. A total of 4, 119 patients (75.65%) in the steroid group died during hospitalization, as compared with 4, 403 patients (80.86%) in the nonsteroid group (adjusted hazard ratio, 0.74; 95% CI, 0.70–0.77; p < 0.0001). The mortality rate at 1 year was significantly lower in the steroid group than in the nonsteroid group (83.54% vs 87.77%; adjusted hazard ratio, 0.73; 95% CI, 0.70–0.76; p < 0.0001). Steroid use during hospitalization was associated with survival to discharge, regardless of age, gender, underlying diseases (diabetes mellitus, chronic obstructive pulmonary disease, asthma), shockable rhythm, and steroid use prior to cardiac arrest. Conclusions: In this retrospective observational study, postarrest steroid use was associated with better survival to hospital discharge and 1-year survival. Abstract : Supplemental Digital Content is available in the text.